(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The review and enhancement of security evaluation parameters for image encryption are crucial in the context of modern cybersecurity. This study provides a comprehensive analysis aimed at improving the robustness and effectiveness of image encryption techniques against evolving threats. It examines current encryption standards and methodologies, identifies vulnerabilities, and proposes enhanced evaluation parameters to strengthen image security. Key focus areas include the assessment of encryption algorithms, key management practices, and the integration of advanced cryptographic techniques. By leveraging a detailed review and synthesis of existing literature, this research aims to contribute actionable insights for researchers, practitioners, and policymakers in enhancing the resilience of image encryption systems. The findings underscore the importance of continuous adaptation and innovation in safeguarding sensitive visual data from unauthorized access and manipulation. This study advocates for a proactive approach to cybersecurity, emphasizing the need for rigorous evaluation frameworks to mitigate emerging risks and ensure the confidentiality and integrity of digital images in various applications.